Efficacy of Telephone Information and Advice on Welfare: the Need for Realist Evaluation. Issue 1 (9th September 2016) - Harding, Andrew J.E.; Parker, Jonathan; Hean, Sarah; Hemingway, Ann
Abstract : In the context of increased marketisation in welfare provision, formal information and advice (I&A) is widely assumed to enable users, as consumers, to make informed choices about services, support and care. There is emerging evidence that telephone I&A services represent important ways of providing such services. This article proposes a framework that identifies key areas of focus delineating the efficacy of I&A, which is then used in a comprehensive literature review to critique existing research on outcomes and/or impact of telephone I&A. Existing, predominately quantitative, research has critical weaknesses. There is a lack of adequate contextual focus, understanding agency, and how I&A is used in different contexts to influence causal processes. The article contends that the efficacy of I&A is not adequately reported and provides much needed theoretical clarity in key areas, including the desirability of further realist evaluation approaches.